Beispiel Nr: 03
$\text{Gegeben:}\\ \text{Bruch1:}\frac{a}{b} \\ \text{Bruch2:}\frac{c}{d} \\ \\ \text{Gesucht:} \\\text{Summe,Differenz,Produkt,Quotient} \\ \frac{a}{b} - \frac{c}{d}\\ \textbf{Gegeben:} \\ a=5 \qquad b=6 \qquad c=2 \qquad d=7\\ \\ \textbf{Rechnung:} \\ \text{Hauptnenner: kgV( }6,7 \text{) }= 42 \\ \text{Erweiterungsfaktoren: }\frac{42}{6}=7 \qquad \frac{42}{7}=6 \\ \\\text{Summe}\\ \frac{5}{6}+\frac{2}{7}=\frac{5\cdot7}{6\cdot7}+\frac{2\cdot6}{7\cdot6}= \frac{35+12}{42}=\frac{47}{42}=1\frac{5}{42} \\ \\\text{Differenz}\\ \frac{5}{6}-\frac{2}{7}=\frac{5\cdot7}{6\cdot7}-\frac{2\cdot6}{7\cdot6}= \frac{35-12}{42}=\frac{23}{42}=\frac{23}{42} \\ \\\text{Produkt} \\ \frac{5}{6} \cdot \frac{2}{7}=\frac{5\cdot2}{6\cdot7}= \frac{10}{42}=\frac{5}{21} \\ \\\text{Quotient} \\ \frac{5}{6} : \frac{2}{7}=\frac{5}{6} \cdot \frac{7}{2}= \frac{35}{12}=2\frac{11}{12} \\ $